The Summer 2006 Lebanese food crisis - Ladki, Said M. (2008)
This article explores major predicaments encountered by the four million people of Lebanon have encountered for thirty-four days of war during the summer of 2006. During the war, Lebanon witnessed land, sea, and air blockade barring all food imports. Furthermore, the country's infrastructure, farmlands, seaports, bridges, and airport were all heavily bombarded and shelled. The blockade and the bombardment created a national food crisis and made it difficult for humanitarian agencies to transport food and aid supplies. Local food distributors were not able to transport goods, and warehouses were either selling out or having their products expire due to the absence of power. Being a nation that lacks a food policy and always susceptible to war, the country needs to create a food policy in order to maintain acceptable quality of life during difficult times.